A new approach of the visibility calculation of an object. (5th January 2005) - Derigent, William; Remy, Sebastien; Ris, Gabriel
Currently, algorithms of mechanical part visibility determination are slow, because the part surface is cut into numerous elementary surfaces. In this article, we propose to take into account the visibility properties of convex and concave surface patches, in order to treat the object in a global way. This new method is studied on 2D curves; 3D extension is considered.